ERIOCAULON BIAPPENDICULATUM, A NEW SPECIES OF ERIOCAULACEAE FROM THE SOUTHERN WESTERN GHATS, INDIA - Manudev, K. M.; Robi, A. J.; Nampy, S. (Edinburgh Journal of Botany, 2015)
Eriocaulon biappendiculatum, a new species of Eriocaulaceae from the southern Western Ghats, India, is described and illustrated. The new species is close to Eriocaulon nairii but differs in having 5–17 peduncles, free male sepals, and both continuous ribbon-like and setiform appendages on the seeds.
Keywords: Endemic; Eriocaulaceae; Kerala; Munnar; southern Western Ghats